EMPRESAS JUNIORES: O PROCESSO DE INSTITUCIONALIZAÇÃO EM UNIVERSIDADES PÚBLICAS DOCEARÁ - Emanuel Dheison dos Santos Penha; Mariana de Melo Alexandre; Augusto Cézar de Aquino Cabral; Sandra Maria dos Santos; Maria Naiula Monteiro Pessoa (Revista Gestão Universitária na América Latina, 2015)
This research aims to investigate the process of institutionalization of Junior Enterprises (JEs)of the publicuniversities of Ceará, according to the model of institutionalization of Tolbertand Zucker (1999) in its three phases: habituation, objectification and sedimentation. Thisresearch is bibliographic, being classified as a descriptive study of qualitative and quantitativenature. The study was conducted in 10 JEs of Ceará. During data collection, questionnairesadministered with members, and interviews with the presidents of the JEs were used. Theresults show that the main reason for the emergence of IOs in public universities of Ceará wasthe need to combine theory with practice, the main actors in the process of these entities werestudents. No resistance groups, but there is a threat at the prospect of continuity due to highturnover in JEs. The JEs are among the phases of objectification and sedimentation andisomorphic characteristics, among JEs, are related to the sharing of best managementpractices.